ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI PT. KERETA API INDONESIA (PERSERO) DAOP 5 PURWOKERTO DENGAN PARTIAL LEAST SQUARE - Jajang Jajang; Supriyanto Supriyanto; Dimas Eka Putra (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
In this research, PLS method is applied to analyze which factor are affect employee performance in PT. Kereta Api Indonesia (Persero) DAOP 5 Purwokerto based on variables that are research factors that is employee performance, work motivation, leadership, training, work enviroment and corporate culture through the indicator which are then analyzed. From analysis using a PLS method with 6 variables of research, it was found that R-square value work of motivation variables of 77,00% with good assessments defined by construct variable of leadership, training, work enviroment and corporate culture while another 23% is described by other variables outside this research. The value of R-square on employee performance variables of 66,00% with good enough assessment criteria described by the work of motivation, where as another 34% is described by other variables outside this research model.